PERSELINGKUHAN ETHAN FROME DENGAN MATTIE SILVER DAN KONFLIK YANG MENYERTAINYA DALAM NOVEL ETHAN FROME KARYA EDITH WHARTON - Dikanovi, Vicky (LANTERN (Journal on English Language, Culture and Literature), 2012)
This thesis talks about a love affair, but this affair is different from the common love affairs. This scandal is not with people out of their environment but with a step cousin. This research is based on Ethan Frome novel by Edith Wharton and the affair that happens is between Ethan Frome and Mattie Silver, the cousin of Zenobia Pierce. Zenobia Pierce is Ethan Frome’s wife. The purpose of this research is to analyze the characters in the novel with their internal and external conflicts, and to express the love affair they have. In writing this thesis, the writer applied several methods, namely library research to collect data and information related to the thesis and structural approach method to analyze the characters and conflicts, psychological approach method to analyze the love affair that happens in this novel. The result of this study shows that Ethan makes a love affair scandal and the love affair scandal does not end happily.